2023
DOI: 10.1111/vco.12931
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors influencing death prior to discharge in 302 dogs undergoing unilateral adrenalectomy for treatment of primary adrenal gland tumours

Hunter J. Piegols,
Brittany E. Abrams,
Janis M. Lapsley
et al.

Abstract: Adrenalectomies for canine adrenal tumours are associated with peri‐operative morbidity and mortality. Objectives of this study included assessing the prognostic value of tumour‐ or surgery‐related variables in predicting peri‐operative mortality and overall survival in dogs undergoing adrenalectomies for primary adrenal tumours as well as pre‐treatment with phenoxybenzamine on survival to discharge with pheochromocytomas specifically. A multi‐institutional retrospective cohort study was performed across nine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Importantly, in this study, the authors also found no effect on intraoperative cardiovascular stabilization. Moreover, more recent literature did not support the preoperative phenoxybenzamine administration in dogs undergoing phaeochromocytoma excision, since no reduced mortality was found ( Appelgrein et al ., 2020 ; Enright et al ., 2022 ; Piegols et al ., 2023 ). These three studies question the Herrera et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, in this study, the authors also found no effect on intraoperative cardiovascular stabilization. Moreover, more recent literature did not support the preoperative phenoxybenzamine administration in dogs undergoing phaeochromocytoma excision, since no reduced mortality was found ( Appelgrein et al ., 2020 ; Enright et al ., 2022 ; Piegols et al ., 2023 ). These three studies question the Herrera et al .…”
Section: Discussionmentioning
confidence: 99%
“…Even though a 2-week treatment was generally recommended to achieve complete α-blockade preoperatively ( Herrera et al ., 2008 ), it was administered for 1 week only in the present case. This was not considered a major concern, as recent literature generally does not support their use ( Appelgrein et al ., 2020 ; Enright et al ., 2022 ; Piegols et al ., 2023 ). Nevertheless, normotension was never achieved preoperatively, despite the concomitant administration of prazosin and amlodipine, a calcium channel blocker.…”
Section: Discussionmentioning
confidence: 99%